CPAS: Surgical approach with combined sublabial bone resection and inferior turbinate reduction without stents. (4th December 2014) - Merea, Valeria S.; Lee, Andrew H. Y.; Peron, Didier L.; Waldman, Erik H.; Grunstein, Eli
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Congenital pyriform aperture stenosis (CPAS) is a form of nasal obstruction caused by congenital narrowing of the maxilla at the medial processes. Traditionally, surgical correction involves a sublabial approach with subperiosteal dissection, widening of the aperture by drilling, and the use of nasal stents postoperatively. Although this approach may lead to symptomatic improvement, it alone may fail to provide a patent airway secondary to unaddressed posterior narrowing. Additionally, the use of stents is problematic because they are prone to clogging and can cause internal nasal scarring and septal or alar necrosis. We present the surgical management of this condition in six patients using a novel approach that aims to correct these limitations by including both the traditional sublabial procedure and an endonasal reduction of the inferior turbinates, without the use of stents postoperatively. Study Design Retrospective chart review. Methods Review of the medical records of six consecutive patients aged 2 weeks to 7 months, who underwent repair of CPAS via a sublabial ostectomy and endonasal inferior turbinate reduction from 2009 to 2012. Results All six patients were clear of airway obstruction postoperatively and at follow‐up. Conclusion This is an alternative approach that leads to symptomatic improvement for CPAS patients without the morbidity associated with stent use. Level of Evidence 4. Laryngoscope, 125:1460–1464, 2015